The lady travelers guide to deception with an unlikely earl - Alexander, Victoria (Alexander, Victoria. Lady Travelers Society., 2018)
Harry Armstrong has spent years in Egypt, recovering relics and disregarding rules. Now he<U+2019>s back in England with a new title and a new purpose: penning his exploits. But his efforts are overshadowed by London<U+2019>s favorite writer about Egypt<U+2014>a woman they call The Queen of the Desert, of all things. Worse, her stories<U+2014>serialized in newspapers and reprinted in books<U+2014>are complete rubbish. Miss Sidney Honeywell didn<U+2019>t set out to deceive anyone. It<U+2019>s not her fault readers assumed her Tales of a Lady Adventurer in Egypt were real! Admitting her inadvertent deception now would destroy her reputation and her livelihood. But when the Earl of Brenton challenges her to travel to Egypt to prove her expertise, accompanied by his dashing, arrogant nephew, what choice does she have but to pack her bags? With the matchmaking founders of the Lady Travelers Society in tow, Harry is determined to expose Sidney<U+2019>s secret. But the truth might not be as great a revelation as discovering that love can strike even the most stubborn of hearts.